Patogenicidade de três grupos de Acanthamoeba pertencentes a genótipos distintos: avaliação in vitro e in vivo. - Norberto de Souza Fernandes (2019)
Amoebas of the genus Acanthamoeba are free-living protozoa considered opportunistic pathogens, since in some situations they can cause serious infections in humans. Besides a severe and usually fatal brain infection, Acanthamoeba is also associated to a progressive corneal infection, the Acanthamoeba keratitis (AK). Currently, pathogenic and non-pathogenic strains are recognized among samples of Acanthamoeba, which can be classified by molecular methods and biological tests. The objective of this work was to evaluate three Acanthamoeba strains from three different morphological groups and genotypes through an in vitro pathogenicity test (erythrophagocytosis) and an experimental model of amoebic keratitis in Wistar rats. Three axenic cultures of strains isolated from a patient with keratitis (Krt2 group II / T4 genotype, PEN group III / T5 genotype) and from the environment (SoA1 group I / T17 genotype) were used. Krt2 strain associated with lethally irradiated Escherichia coli was also included in the experiments. In the in vitro assay, trophozoites were interacted with human erythrocytes in 1:100 ratios for 20 minutes. The mean values of erythrophagocytosis were 25.3%, 11.3%, 0.33% and 11.3% for Krt2, PEN, SoA1 and Krt2 + E. coli Irrad samples, respectively. In the in vivo assay, intrastromal inoculations of 2.5 x 104 trophozoites in Wistar rats were performed. The infectivity of each sample was determined, as well as the nature of the lesions and the presence of amoebas, which were investigated by histopathology and immunohistochemistry. Only SoA1 strain caused corneal lesions in two rats (n=9). The lesion grades were 1 and 3 and the rat with more severe lesion developed ulcerated keratitis. The lesions were characterized by an inflammatory process typical of Acanthamoeba infections. Hyperimmune serum produced in Wistar rat with antigens of a T4 genotype strain was used in immunocytochemical technique, which confirmed the labeling of trophozoites. In the histological sections, cysts were not seen. A large amount of Acanthamoeba immunoreactive antigenic residues were observed in both rats with keratitis, suggesting that the inflammatory process was in resolution of the infection. In conclusion, Acanthamoeba is able to phagocyte human erythrocytes at low intensity and the Acanthamoeba keratitis model in Wistar rats presented a low infection rate under the conditions adopted in this study. However, the ability of Acanthamoeba group I genotype T17 to cause corneal infections was showed in this study, which also allowed to establish the efficiency of immunocytochemical and immunohistochemical method, with prospects to be used for standardizing a diagnostic test.